Peranan Gerakan Pramuka dalam Mengembangkan Nilai-Nilai Kristiani di My Little Island (MLI) Elementary School, Malang - Intansakti Pius (Jurnal Penelitian Pendidikan Agama Katolik, 2021)
This study aims to determine the extent of the role of the scout movement in developing Christian values ​​at My Little Island (MLI) Elementary School Malang. This nature of this research is quantitative research. The variable was singular: the role of scout movement in developing christian values in My Little Island (MLI) Elementary School Malang. The sampling method was purposive sampling. Close questionnaires, utilizing google forms, were distributed for data collection. The samples of this research were all christian boys and girls, catholics and protestants, of 4th – 6th Grade of MLI. The method for data analysis was descriptive quantitative. As the research concluded, the overall score regarding the role of the scout movement in empowering the christian values at MLI was 4.22. This result corresponded in the interval of 4.21-5.00, which was very good. Based on the result, MLI was recommended to continue integrating the scout movement or other similar programs for it was proven that such activities were effective in developing christian values of the students in practical level. Qualitative research with direct observations and interviews with key informants should be conducted to complement this research.